Pemetaan Tantangan dan Kebutuhan Penyuluh Pertanian dalam Upaya Peningkatan Kualitas Penyuluhan Pertanian - Fara Shaliza (Yayasan Literasi Sains Indonesia, 2025)
Agricultural extension agents play a strategic role in improving the quality of agricultural extension services and supporting sustainable agricultural development. However, in practice, extension agents face various challenges that can limit the effectiveness of field-level extension activities. This community service program aimed to identify the challenges faced by agricultural extension agents, map their actual needs, and formulate priority scales to address them, thereby improving the quality of agricultural extension services. The activity was conducted at the Agricultural Extension Center (BPP) of Dumai Selatan District, Dumai City, involving agricultural extension agents as the main partners. A participatory approach was applied through focused group discussions (mini FGDs), combined with awareness-building activities, capacity enhancement, and consultation and mentoring. The results indicate that the challenges faced by extension agents are multidimensional, covering structural, technical, institutional, and psychosocial aspects. The primary needs identified include capacity building through relevant and continuous training, support for extension facilities and infrastructure, and the strengthening of institutional coordination. Through collective deliberation, a priority scale of needs was formulated as a key output of the program. The activity was supported by the active participation and openness of extension agents, though it was constrained by limited time due to their workload. Overall, this community service activity produced a contextual mapping of extension agents’ challenges and needs, which can serve as a practical basis for planning more targeted and sustainable agricultural extension strengthening programs.